ChemInform Abstract: Iodine‐Mediated Synthesis of Aromatic Thioethers with Aromatic Amines and Sulfonyl Hydrazides in High Regioselectivity via C(sp2)—H Bond Functionalization. Issue 23 (May 2016) - Pang, Xiaobo; Xiang, Likui; Yang, Xiaodong; Yan, Rulong
Abstract: A convenient synthesis of bis(aryl) thioethers having a para‐amino substituent is rendered possible by a highly regioselective oxidative C—H coupling of N, N‐disubstituted anilines with arylsulfonyl hydrazides.